Comparison between Two Zurich Cementless Total Hip Replacement Cup Impactor Types in the Accuracy of Cup Positioning: An In Vitro Study - Mancusi, Davide; Peirone, Bruno; Gallorini, Francesco; Terrana, Mattia R.; Piras, Lisa A. (Veterinary and Comparative Orthopaedics and Traumatology, 2025)
This study aimed to investigate the influence of cup positioning accuracy of two different cup impactors handled by two surgeons with different levels of total hip replacement surgery experience.This was a cadaveric study (n = 20). A standard and a new prototype Kyon impactor were used by two surgeons (beginner and senior) to impact 80 prosthetic cups in 40 canine normal acetabula. The angle of lateral opening, angle of cup retroversion, and their corresponding deviations from the ideal postoperative values were measured using radiographic imaging to evaluate the accuracy of cup positioning.The accuracy of cup positioning was not affected by the type of impactor used by the senior surgeon. For the beginner surgeon, the standard impactor was associated with a significantly higher mean error (3.9 ± 6.5 degrees) and mean value (48.90 ± 6.5 degrees) for the angle of lateral opening compared with the prototype impactor that showed a lower mean error (−1.8 ± 6.3 degrees) and mean values (43.20 ± 6.34 degrees) closer to the ideal value of 45 degrees. No significant differences were found between the standard impactor and the prototype regarding the accuracy of the angle of cup retroversion.The new features of the prototype impactor and its improved handling can assist inexperienced surgeons in achieving a more accurate angle of lateral opening compared with the standard impactor. In contrast, the accuracy of the cup retroversion angle appears to be more closely related to the surgeon's experience rather than the type of impactor used.
Keywords: cup positioning accuracy; total hip replacement; dog; cup impactor; Zurich cementless total hip replacement